Penggunaan Boron untuk Meningkatkan Pertumbuhan, Hasil, dan Kandungan Minyak Kacang Tanah - Linayanti Darsana; Pardono Pardono; Hermawan Sugianto (Universitas Sebelas Maret, 2014)
Ground nut (Arachis hypogaea) is a seasonal crop that have been cultured in many place as for interspace crop or as monoculture crop. Though the demand of ground nut is high, its yield productivity not optimal and still considerate as moderate. Therefore, a new treatment is needed. Boron is one of essensial nutrition for plant that rarely used when planting, although boron have many function including to increase plant productivity. This research is purposed to see about boron influence in the ground nut productivity and fat contain on it. The result of the research showed boron can increase the flowering time of ground nut. The result of ground nut productivity not shown any significant differences, but inclined to had increased productivity up to 20% than control in 5 mg B2O3 dosage and keep decreasing as the boron dosage increased. Boron also have real influence in increasing the ground nut seed quality with the increased of gound nut weight, and the calculation of fat contain in ground nut that also increased as the boron dosage increased.